Metanephric adenoma: the utility of immunohistochemical and cytogenetic analyses in differential diagnosis, including solid variant papillary renal cell carcinoma and epithelial-predominant nephroblastoma - Kinney, Stephanie N; Eble, John N; Hes, Ondrej; Williamson, Sean R; Grignon, David J; Wang, Mingsheng; Zhang, Shaobo; Baldrige, Lee Ann; Martignoni, Guido; Brunelli, Matteo; Wang, Lisha; Comperat, Eva; et al. (Modern pathology, 2015)
Metanephric adenoma is a benign renal neoplasm that overlaps in morphology with the solid variant of papillary renal cell carcinoma and epithelial-predominant nephroblastoma. To aid in resolving this differential diagnosis, we investigated the utility of immunohistochemical and molecular analyses in distinguishing between these entities; the first study, to our knowledge, to use a combined approach in analyzing all three tumors. We analyzed 37 tumors originally diagnosed as metanephric adenomas (2 of which we reclassified as papillary renal cell carcinomas), 13 solid variant papillary renal cell carcinomas, and 20 epithelial-predominant nephroblastomas using a combination of immunohistochemistry and fluorescence in situ hybridization (FISH) assessing for trisomy of chromosomes 7 and 17 and loss of Y. Immunohistochemical staining was performed for CK7, AMACR, WT1, and CD57. The combination of CK7-, AMACR-, WT1+, and CD57+ was considered characteristic of metanephric adenoma. Most of the tumors originally diagnosed as metanephric adenomas (31/37) showed the expected staining pattern of metanephric adenoma (CK7-, AMACR-, WT1+, and CD57+). Of the six tumors with discordant immunophenotype, two tumors were reclassified as papillary renal cell carcinoma after cytogenetic workup. It is recommended that all adult cases histologically resembling metanephric adenoma have WT1, CD57, CK7, and AMACR immunohistochemical staining performed. If the staining pattern is characteristic for metanephric adenoma (CK7-, AMACR-, WT1+, and CD57+, including membranous staining), then no other diagnostic tests are indicated. However, if there is a different immunostaining pattern, then we recommend FISH analysis.
Keywords: nádory ledvin; Humans; diferenciální diagnóza; lidé středního věku; dítě; cytogenetické vyšetření; In Situ Hybridization, Fluorescence; Biomarkers, Tumor; Child; Female; Aged; mladý dospělý; dospělí; Diagnosis, Differential; senioři; lidé; Immunohistochemistry; imunohistochemie; nádorové biomarkery; Adult; ženské pohlaví; Male; hybridizace in situ fluorescenční; Middle Aged; Wilmsův nádor; Aged, 80 and over; adenom; Adenoma; karcinom z renálních buněk; Young Adult; senioři nad 80 let; Carcinoma, Renal Cell; Cytogenetic Analysis; mužské pohlaví; Kidney Neoplasms; Wilms Tumor